(3QhVI GdCRgGQ hHgLI GdfahS hfRgI GdCHUGQ GdLGeYI dafhf GdBOH hSMQ GdCdHGHs - (3GdMSf Hf Ydj Hf Nda GdCehj, CHh Ydj, GdeYQha HGdNWjH,J (B602 (3g` s
(3ChdgG (B:s
(3hHYO Ef Gdhdi GdCcQe hGdYeGO GdCYXe , aEf Ghd eG QHWJ Hg GdfahS hCPgH Hg GdYHhS eLGdSI Cgd GdYde hLGdSI Cgd Gdabg s
(3BNQgG (B:s
(3aHGQcJ bUQJ Yf fgGjI ChHdhZ ZGjI ajbOQ GdYde hGdOQGjI hgPG GdLgO LgO Gdebd GdeLJgO hGddg jHZfi hGjGc ZGjI GdSDGd hGdBeGd Yfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B253s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B50 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdedcjI (B- (3GdQHGW (B(2543) s
Keywords: (3GdCOHs